Chemical composition and electronic structure of anodic passive films on low-C 13CrNiMo stainless steel - Gervasi, Claudio Alfredo (2016)
Mott–Schottky analysis and electrochemical and X-ray photoelectron spectroscopy (XPS) measurements were performed on passive films formed on low-C 13CrNiMo stainless steel with different applied heat treatments. Heat treatments render particular microstructural features of the alloy with a significant impact on the ability of the passive films to afford adequate protection against localized corrosion. A lower level of retained austenite in the substrate renders thinner passive films. Phosphates coexist with oxidized Fe(III) compounds as the prevailing species in the anodic layers. Mo was only detected in the oxide film formed on the sample with a higher retained austenite content. Passive layers behave as n-type semiconductors with two types of donors, namely, shallow-level and deep-level states. The observed flat band potential VFB≅ -0.425 ± 0.005 V vs. standard calomel electrode (SCE) is independent of the thermal treatment of the alloy but under potential bias conditions at the corrosion potential the occurrence of the cathodic reaction on the oxide surface is hindered on the sample with higher retained austenite in its microstructure as compared to the sample with lower retained austenite content.